Challenges and enablers faced by HIV/AIDS supporting organizations during COVID-19 - Nyadenga, Dorcus; Davis, Burt (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2023)
The dynamics of multi-sectoral collaborations between HIV/AIDS-supporting non-governmental organizations and public health institutions can significantly affect how programs are implemented, especially during emergencies like the once-in-100-year COVID-19 pandemic. These collaboration dynamics were explored in a South African context in the Western Cape province during COVID-19. Interviews and a focus group discussion were conducted with participants (n=6) from two small-scale HIV/AIDS-supporting NGOs and one public health institution. Challenges of multi-sectoral collaboration identified included inadequate engagement opportunities, limited opportunities to contribute during engagements, and being forced to innovate to survive. Enablers of multi-sectoral collaboration, such as communication, leadership, coordination of responsibilities, and trust and transparency, were found to be crucial for effective and strong working relationships during times of unparalleled disaster. New insights are offered on how enablers of collaboration that apply during normal circumstances should be thought of during times of crisis, and how these can be adapted and augmented to help HIV/AIDS collaborative partnerships survive future potentially disastrous situations like climate change.